Sinus node dysfunction in children and adolescents: treatment by implantation of a permanent pacemaker in 26 patients - Kardelen, Fırat; Çeliker, Alpay; Özer, Sema; Özme, Şencan; Oto, Ali (The Turkish Journal of Pediatrics, 2002)
Sinus node dysfunction has been reported rarely in pediatric patients with structurally normal hearts. It has been diagnosed with increasing frequency in children and young adult patients with congenital heart defect, especially in patients who have undergone corrective cardiac surgery related with atrial tissue.Between 1984-1999, 26 patients who were under 22 years of age underwent implantation of a permanent pacemaker for treatment of sinus node dysfunction at our medical center. This subset of patients represents 18.5% of all patients who required permanent pacemakers during this time. The mean age of the 17 male and 9 female patients at initial implantation was 9.2±6 years (range, 0.5 to 22 years). Of the 26 patients, 18 (69%) had associated cardiovascular disease and in 11 (34.6%) patients, sinus node dysfunction developed after a cardiac operation.The patients were followed up for a total 1,227 (47±45, range 2-176, median 34) pacing months. All symptomatic patients noted a resolution of symptoms after pacing had been performed, and they remained free of symptoms at the latest follow-up examination. Mean acute pacing thresholds and mean latest pacing thresholds for the endocardial atrial and ventricular leads, mean acute impedance and mean latest impedance for the endocardial atrial and ventricular leads and mean acute p wave voltage and the latest p wave voltage did not differ significantly.In this report, we review our experience in children who required implantation of a permanent pacemaker for treatment of sinus node dysfunction during a 15-year period.
Keywords: sinus node dysfunction; children; adolescents; permanent pacemaker implantation